A cognitive analysis of an English reading test through the G-DINA model. (September 2020) - Zhao, Haizhen; Wang, Weize; Huang, Yuyuan
Abstract: The development of language testing calls for more in-depth diagnostic information of language skills to provide targeted feedback for test developers and test takers as well. Cognitive diagnostic assessment is capable of evaluating language skills (cognitive attributes) involved in a language test and assessing the cognitive features of test takers. Therefore, the introduction of cognitive diagnostic assessment to language testing is of great significance. The study is aimed to make a cognitive analysis of an English reading test for first-year college students through a cognitive diagnostic model named G-DINA. Through the feedback information of cognitive analysis, the study is expected to provide scientific and targeted feedback for students and teachers, helping to improve language testing, teaching and learning.